Current advances of Polyurethane/Graphene composites and its prospects in synthetic leather: A review. (5th December 2021) - Zhu, Xueli; Li, Qiuyi; Wang, Liang; Wang, Wei; Liu, Shengkai; Wang, Chunhong; Xu, Zhiwei; Liu, Liangsen; Qian, Xiaoming
Graphical abstract: Highlights: The latest advances of polyurethane/graphene composites including their properties and challenges in the fields of thermal conduction and flame-retardance, antimicrobial, ultraviolet resistance, electromagnetic interference shielding, and oil–water separation are widely presented. The preparation process, applications and prospects of the PU/graphene composites in high-performance synthetic leather are summarized in this review. Functionalization of polyurethane and graphene nano-derivatives including covalent and noncovalent modifications of the composites are covered. We put forward some novel speculations for the composites and their synthetic leather manufacture in advanced areas. Abstract: In recent years, polyurethane/graphene composites (PUGs) have attracted considerable attention attribute to their wide applications ranging from industrial manufacturing to bioengineering. The addition of graphene-based derivatives to the PU matrix can improve the mechanical, thermal, and electromagnetic properties, etc., to meet the specific demands of quality, functionality, and novelty of polymer composites. There are different modification methods of graphene and structural designs of polyurethane matrix for the applications of PUGs in various areas. Among the major applications, PUGs possess remarkable features in the dipping and coating process of synthetic leather. However, limited comprehensive summaries of functional PUGs have been published in broad fields and synthetic leather. The review aims to provide an overview of the cutting-edge developments of PUGs in the properties of thermal conduction and flame-retardance, antimicrobial, ultraviolet resistance, electromagnetic interference shielding, and oil–water separation respectively, which path a way for researchers to apply these uniquely functional composites for high-performance and advanced applications. And the applications of the PUGs in high-physical synthetic leather and the current challenges and prospects of synthetic leather in advanced fields are briefly presented.